PEMBUATAN SOSIAL MEDIA ALUMNI INFORMATIKA UNIVERSITAS SURABAYA BERBASIS WEB - Leon Hartono; Andre Andre; Daniel Soesanto (Perpustakaan Universitas Surabaya, 2018)
Universitas Surabaya (UBAYA) has many Informatics Engineering alumni from various cities in Indonesia. Informatics Engineering department currenty has no facilities to accomodate the alumni to maintain communication within each others. Moreover, alumni face problem in doing job search because it is difficult to find vacancies suitable to their field. It is also difficult to search freelance software or system development projects.Based on that current problems, the department needs a system as a medium to gather alumni in order to establish communication within each othersand provide features which can help alumni find jobs in accordance with their desired field. The system created is a special social media alumni of Informatics Engineering of Universitas Surabaya by providing job search feature and freelance projects.Features on this system is made based on requirements obtained from analysis of similar system. From the validation of this system, it is concluded that the system is able to meet the requirements of alumni in terms of expanding and strengthen alumni relation within each others, and also facilitates alumni to search jobs and freelance projects.